CCSP cisco secure VPN exam certification guide : - Roland, John F. (Cisco Press, 2003)
CCSP Cisco Secure VPN Exam Certification Guide is a comprehensive study tool that enables you to master the concepts and technologies required for success on the CSVPN exam. Each chapter of the CCSP Cisco Secure VPN Exam Certification Guide tests your knowledge of the exam subjects through sections that detail exam topics to master and areas that highlight essential subjects for quick reference and review. Challenging chapter-ending review questions and exercises test your knowledge of the subject matter, reinforce key concepts, and provide you with the opportunity to apply what you've learned in the chapter. In addition, a final chapter of scenarios pulls together concepts from all the chapters to ensure you can apply your knowledge in a real-world environment. The companion CD-ROM testing engine enables you to take practice exams that mimic the real testing environment, focus on particular topic areas, and refer to the electronic text for review. This book is part of a recommended learning path from Cisco Systems that can include simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press.